Suspension of U.S. support for Peru's public health programs: Implications and concerns - Benites-Ibarra, Christeam Anndy (2025)
The recent suspension of U.S. government support for various health and development programs in Latin America highlights the risks of dependence on foreign cooperation. This decision compromises Peru's progress in public health, particularly in strategic areas such as HIV prevention, tuberculosis control, and the elimination of communicable diseases. Despite the historical dependence on international cooperation, USAID reports have highlighted the potential for self-sustainability of the programs implemented in Peru. However, the suspension of foreign support significantly impacts on the development of activities that favor health care coverage, continuity of services, and research capacity in public health. These effects could be sustained in the long term, with consequences that are difficult to reverse if compensation measures or national strengthening strategies are not adopted.